2019
DOI: 10.3390/ijms20184398
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase CK2—A Putative Target for the Therapy of Diabetes Mellitus?

Abstract: Since diabetes is a global epidemic, the development of novel therapeutic strategies for the treatment of this disease is of major clinical interest. Diabetes is differentiated in two types: type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM). T1DM arises from an autoimmune destruction of insulin-producing β-cells whereas T2DM is characterized by an insulin resistance, an impaired insulin reaction of the target cells, and/or dysregulated insulin secretion. In the past, a growing number of studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 108 publications
(132 reference statements)
1
19
0
Order By: Relevance
“…The role of CK2 in glucose homeostasis is well documented and exerted at multiple levels, i.e., from the control of insulin expression and release to its role in pancreatic β-cell turnover. These and other aspects of the CK2-mediated control of endocrine pancreas physiology have been extensively discussed by Ampofo et al in a recent review [ 172 ].…”
Section: The Role Of Ck2 In Lipid Metabolismmentioning
confidence: 99%
“…The role of CK2 in glucose homeostasis is well documented and exerted at multiple levels, i.e., from the control of insulin expression and release to its role in pancreatic β-cell turnover. These and other aspects of the CK2-mediated control of endocrine pancreas physiology have been extensively discussed by Ampofo et al in a recent review [ 172 ].…”
Section: The Role Of Ck2 In Lipid Metabolismmentioning
confidence: 99%
“…With more than 500 substrates, CK2 is involved in various biological processes and estimated to be responsible for up to 10% of the human phosphoproteome [ 2 , 3 ]. CK2 exerts oncogenic activity, because its overexpression promotes tumor development and progression via the activation of proliferation and inhibition of apoptosis [ 4 , 5 , 6 ]. Hence, a broad spectrum of CK2 inhibitors have been developed as potential anti-cancer drugs, including CIGB-300 [ 7 ], 4,5,6,7-tetrabromobenzotriazole (TBB) [ 8 ] and CX-4945 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…CK2 has been shown to be critical in embryonic development, differentiation, immunity, cell survival, epithelial homeostasis and circadian rhythms (4)(5)(6)(7). CK2 is also involved in the etiology of many diseases such as multiple sclerosis, cystic fibrosis, chronic intestinal inflammation, cardiac hypertrophy, atherosclerosis, thrombosis, diabetes mellitus, neurological and psychiatric disorders (7)(8)(9)(10)(11). In cancer, although CK2 by itself is not an oncogene, some studies have confirmed the tumorigenic potential of this kinase by regulating cellular processes that are characteristic of malignant transformation such as cell cycle progression, tumor growth and death resistance (12).…”
Section: Introductionmentioning
confidence: 99%